A Literature Review of Networking Research in Insurance - Liu, Ming (Advances in Social Sciences Research Journal, 2022)
The role of insurance institutions in the economic network is no longer only that of a loss compensator, but also of a risk transfer intermediary and supervisor of payer. In this process, insurance institutions gradually established their status as credit centre. Numerous theoretical studies and practices show that with the development of society, insurance has increasingly become an important factor and even one of the driving forces for economic development. Insurance reflects its value and status in many ways, whether it is the basic social security function or the indispensable importance of ensuring the smooth operation of business. It is worth noting that in recent years, the reform of the medical system has aroused the attention to the phenomenon of "narrow network", which is just for further study of insurance institutions (companies, institutions) and economic individuals (natural persons, The interaction between institutions) provides an opportunity. This paper strives to summarize and reflect the frontiers and dynamics of insurance network research in recent years, and expects to lead to the focus and direction of future insurance research at one time, and expects to provide new ideas and new paths.